Experimental Research and Numerical Simulation of Coal Char-Catalyzed CO2 Reforming of CH4 - Cheng, Haizhu; Zhang, Yongfa; Zhang, Guojie; Song, Sufang (Asian Journal of Chemistry, 2013)
Experimental research and numerical simulation of coal char-catalyzed CO2 reformation of CH4 were done using a small single-hole nozzle reactor. Coal char is known to possess catalytic functions for CH4-CO2 reformation. The computational fluid dynamics software was used to simulate a small-scale reactor for the analysis of temperature distribution, flow field and synthetic gas composition. Simulation results show that the reforming reactor demonstrated good flow field and temperature distribution. The CH4-CO2 reforming areas had higher temperatures that were deemed suitable for the process. The flow field distribution in the reactor showed that O2, CO2 and coke oven gas can be mixed thoroughly to achieve the reaction. The reaction mechanism is a coupling of combustion and reforming reactions at an optimized wall temperature of 1100 K. The H2/CO ratio was about 1.4-3.0 in the synthesis gas, which is the raw material for methanol synthesis.